Low‐temperature selective catalytic reduction of NO over carbon nanotubes supported MnO2 fabricated by co‐precipitation method. (1st November 2015) - Lu, Xiulian; Zheng, Yuying; Zhang, Yanbing; Qiu, Hongfeng; Zou, Haiqiang
Abstract : A series of MnO2 /carbon nanotubes (CNTs) catalysts were prepared to use for the selective catalytic reduction (SCR) of NO with NH3 via liquid‐phase redox method at ambient temperature. The resulting samples possessed an amorphous MnO2 and, a higher SCR activity than that obtained by wet impregnation technique.